Exploring the Feasibility of Wearable Technologies to Provide Interactive Telepresence Sub-Specialist Support to Remote Clinicians Treating Patients with Traumatic Injuries. Issue Volume 34:Issue s1(2019) (May 2019) - Santomauro, Chiara; McCurdie, Tara; Pollard, Cliff; Shuker, Matthew
Abstract : Introduction: Some patients presenting to rural or regional hospitals may be deteriorating so rapidly that emergency procedures might be necessary before transfer to specialist facilities. Such interventions might include placement of an ICC, establishing a surgical airway, evacuation of an EDH, laparotomy, or intra-abdominal packing. The treating clinician may have had little or no experience in the procedure. Interactive telepresence technology offers further point of care support to the treating clinicians through the virtual presence of a specialist from a major trauma center. Aim: To explore the feasibility of wearable interactive telepresence technology that can provide sub-specialist support to remote clinicians treating patients with traumatic injuries. Methods: Thirty-seven wearable near-field display devices and annotation software applications were tested against a set of pre-specified technical and user experience requirements. A shortlist of three devices and two software applications underwent usability evaluations with a convenience sample of 24 junior clinicians and sub-specialists. The junior clinicians trialed the wearable devices and the sub-specialists trialed the annotation applications in three simulated trauma scenarios. Measures included participants' ratings of acceptance and workload, technical issues encountered (e.g. frequency of call drop-outs), and anecdotal comments. Results: Participants' subjective ratings of the solutions and anecdotal feedback were positive. However, there was no clear solution that satisfied the functionality and ease-of-use requirements for all participants. For example, the solutions that were rated more favorably by the junior clinicians were rated less favorably by the sub-specialists, and vice versa. Discussion: This work provided preliminary evidence of the feasibility and usefulness of interactive telepresence technology in healthcare. A second phase of usability testing is currently underway to explore additional device and software combinations, including those with augmented reality functionality. Future phases of the project will evaluate the solutions under higher-fidelity conditions followed by in-situ trials across selected regional centers.